SWOT ANALYSIS OF PROMOTIONAL STRATEGIES IN THE DEVELOPMENT OF RAHMAT ZOO & PARK TOURIST ATTRACTION IN SERDANG BEDAGAI REGENCY SERDANG BEDAGAI - Sintya Rotua Uli Br Pardosi; Simson Ginting (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Serdang Bedagai Regency is one of the areas famous for its tourism, both beach tourism and unique conservation tourism and has become one of the trendy places for tourist visits, namely Rahmat Zoo & Park. However, there are still some weaknesses that are a problem in its development, namely the lack of unique animals such as elephant tigers lions and other unique animals and cleanliness in attractions that still need to be maintained and the promotion of this attraction is also still not optimal and reaches all circles, especially parents. This study aims to determine the promotional strategy in the development of the Rahmat Zoo & Park tourist attraction in Serdang Bedagai Regency. This research uses a qualitative descriptive approach with data collection techniques, namely interviews, observation and documentation. The indicators used are promotional strategies in the development of tourist attractions according to David (2015) there are 4 (four), namely strengths, weaknesses opportunities and threats. The results of this study show that Rahmat Zoo & Park has great potential with various attractions and attractive facilities as well as support from the local government. However, there are several challenges that need to be overcome, such as the lack of step animal collections, not optimal cleanliness, and promotions that have not reached all circles of society, especially parents.